ANALISIS PARAMETER FISIKA-KIMIA UNTUK KEPENTINGAN REHABILITASI EKOSISTEM MANGROVE DI PESISIR PULAU BUNGKUTOKO KOTA KENDARI - Asramid Yasin (Program Studi Manajemen Lingkungan, 2019)
Abstract In some places rehabilitation of mangrove areas that have been damaged but in reality not all mangrove rehabilitation activities were successful, this was allegedly caused by a mismatch in the type of mangrove and incompatibility of rehabilitation techniques used with environmental conditions or parameters of the local coastal environment. This study is aimed to know the condition of coastal environmental parameters in Bungkutoko island, district of Abeli in rehabilitation proposed of mangrove ecosystem and to find a proper rehabilitation strategy for it can be applied in that area. This study was carried on June to July 2009 in the coastal of Bungkutoko island, Abeli district, Kendari Town. Data in this study is analyzed as descriptively for giving common view of that area. Results of some parameters measured in the area are showed as topographies are 0,1 %, 3 %, 3,2 % for Station I, Station II and Station III, respectively. Substrate particles is more small, and it adhesive force in Station I and II is same medium, and Station III is free. Shoreline of Station I as covered and Station II and Station III are semi covered. The High of waves are 7-17 cm and 8-22 cm for Station II and Station III, as respectively. Fluctuation of tidal is middle, and the tidal type of the shoreline is mix to be diurnal. Water current in all station are Station I = 0,01-0,05 m/s, Station II = 0,01-0,08 m/s, Station III = 0,02-0,1 m/s. Suspension sediments of all stations are 1,97 mg/l, 3,96 mg/l, and 3,10 mg/l for Station I, Station II, Station III, respectively. Salinity in range of 25-35 ppt, and both Station II dan Station III is same ranged on 30-35 ppt. In results of measured some physic-chemical parameters of coastal in Bungkutoko island is suitable for rehabilitation practice of mangrove ecosystem by concern of planting time on the condition of mangrove tree is in having fruits and calm water condition of sea. And also for planting technic is propaguls directly planted to the ground and using seeds on the polybags.